Computational studies on non-succinimide-mediated stereoinversion mechanism of aspartic acid residues assisted by phosphate. (19th March 2018) - Nakayoshi, Tomoki; Fukuyoshi, Shuichi; Takahashi, Ohgi; Oda, Akifumi
ABSTRACT: Although nearly all of the amino acids that constitute proteins arel -amino acids, d -amino acid residues in human proteins have been recently reported.d -amino acid residues cause a change in the three-dimensional structure of proteins, andd -aspartic acid (Asp) residues are considered to be one of the causes of age-related diseases. The stereoinversion of Asp residues in peptides and proteins is thought to proceed via a succinimide intermediate; however, it has been reported that stereoinversion can occur even under conditions where a succinimide intermediate cannot be formed. In order to elucidate the non-succinimide-mediated stereoinversion pathway, we investigated the stereoinversion ofl -Asp tod -Asp catalysed by phosphate and estimated the activation barrier using B3LYP/6−31+G(d, p) density functional theory (DFT) calculations. For the DFT calculations, a model compound in which the Asp residue is capped with acetyl and methyl-amino groups on the N- and C-termini, respectively, was used. The calculated activation barrier was not excessively high for the stereoinversion to occur in vivo . Therefore, this stereoinversion mechanism may compete with the succinimide-mediated mechanism. GRAPHICAL ABSTRACT: